THE USE OF DIFFERENTIATED INSTRUCTION (DI) IN TEACHING READING - Sormin, Putri Handayani (Universitas Samudra, 2025)
The aims of this study to find out whether or not DI is going to improve students reading descriptive text score. This research was conducted in SMP Negeri 9 Langsa. The research was quantitative method by using one-group pretest-posttest pre-experimental design. To collect the data this research employed questionnaire and test as the instruments. The population of this research was six class VIII students in SMP Negeri 9 Langsa and the sample of this study was 28 students of class VIII-2. The data obtained from the pre-test and post-test was analysed through hypothesis testing by using T-test. The pre-test mean score was 48,9 and the post-test score was 71,4. The result of the t-observed value was 11,08. The result was greater than the t-table value in significance 5%, it was t-table = 2,052 and significance 1% value, t-table= 2,771. Thus, the result fits the criteria t-observed > t-table. Therefore, the alternate Hypothesis was accepted. The result shows that there was a significance change on students reading descriptive text score between pre-test and post-test.